2010
DOI: 10.1136/gut.2009.192401
|View full text |Cite
|
Sign up to set email alerts
|

Alarm features and age for predicting upper gastrointestinal malignancy in Chinese patients with dyspepsia with high background prevalence of Helicobacter pylori infection and upper gastrointestinal malignancy: an endoscopic database review of 102 665 patients from 1996 to 2006

Abstract: For uninvestigated Chinese patients with dyspepsia with high background prevalence of H pylori infection and upper GI malignancy, alarm features and age, except for dysphagia in patients between 36 and 74 years old, had limited predictive value for a potential malignancy; therefore, prompt endoscopy may be recommended for these patients. However, less invasive, inexpensive screening methods with high diagnostic yield are still needed to reduce unnecessary endoscopy workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 37 publications
(38 reference statements)
8
80
1
Order By: Relevance
“…In addition, patients suffering from biliary and pancreatic diseases accounted for a large proportion and there were several reasons: firstly, our department is particularly specialized in biliary and pancreatic disorders, which might attract a great proportion of patients. Secondly, the incidence of gastrointestinal tumors was not as high as reported, which was supported by our previous researches [18,19]. Besides, the number of patients The prognosis of early GC is better with a 90% 5-year survival rate, while the advanced GC is relatively poor [20].…”
Section: Discussionsupporting
confidence: 59%
“…In addition, patients suffering from biliary and pancreatic diseases accounted for a large proportion and there were several reasons: firstly, our department is particularly specialized in biliary and pancreatic disorders, which might attract a great proportion of patients. Secondly, the incidence of gastrointestinal tumors was not as high as reported, which was supported by our previous researches [18,19]. Besides, the number of patients The prognosis of early GC is better with a 90% 5-year survival rate, while the advanced GC is relatively poor [20].…”
Section: Discussionsupporting
confidence: 59%
“…2 In Asia, the prevalence of Helicobacter pylori infection and upper GI malignancies are substantially high. 3,4 However, among…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] However, "H. pylori test and treat" was unlikely to be beneficial in the high H. pylori positive area in aspect of cost-effectiveness. 3 This large scale meta-analysis was conducted on the basis of evidence-based medicine in the context of the insufficient existing data and authors clearly revealed important epidemiologic features. The malignancy detection rate in this study was significantly higher than that in Western countries (1.3% vs 0.25%).…”
Section: Commentsmentioning
confidence: 99%
“…The prevalence of peptic ulcer disease confirmed endoscopically could reach to 17.2 % [113] in China, substantially higher than in Western populations. Gastric cancer remains the fourth most common malignancy and the second leading cause of cancer mortality in the world [114].…”
Section: Introductionmentioning
confidence: 97%